The Influence of Mind-Mapping Learning Model on Mathematical Communication Skills and Interests of Students of Elementary School 200110 Padangsidempuan City - Nasution, Suriani; Hasratuddin, Hasratuddin; Anam, Rifat Shafwatul; Syahril, Syahril (Continuous Education: Journal of Science and Research, 2025)
The study aims to analyze the differences in students' mathematical communication skills through the mind mapping learning model better than those given regular learning, analyze the differences in students' interest in learning mathematics through the mind mapping learning model better than those given regular learning, analyze the interaction between learning and students' initial abilities on mathematical communication skills, analyze the interaction between learning and students' initial abilities on students' interest in learning mathematics at Padang Sidempuan City Elementary School. The sample was determined as many as 54 people consisting of 2 (two) classes. The research design used in this study was an experimental design with a 2x3 factorial. The results of the study concluded that students' mathematical communication skills were taught with the mind mapping learning model better than using regular learning. Students' mathematical communication skills have a high learning interest better than those with a low learning interest. There is an interaction between learning and initial mathematical abilities on students' mathematical communication abilities. There is an interaction between learning and initial mathematical abilities on students' learning interests.